Studies in Guatemalan Caelifera: New grasshoppers and monkey grasshoppers (Orthoptera: Caelifera: Acridoidea & Eumastacoidea) and an updated checklist - Cadena-Castañeda, Oscar J.; Monzón-Sierra, José (Zootaxa, 2014)
We describe six species of Acridomorpha, Orthoptera from Guatemala: Paralethus rowelli n. sp., Paralethus cerezoi n. sp., Episactus schusteri n. sp. (Episactidae: Episactinae), Pararhicnoderma eniocanoi n. sp. (Romaleidae: Bactrophorinae), Tela neumanni n. sp. and Leioscapheus faustinoi n. sp. (Acrididae: Proctolabinae). four genera and five species are recorded for Guatemala and, at the same time a checklist is provided for Caelifera species found so far in the country.